The recombinant spike S1 protein induces injury and inflammation in co-cultures of human alveolar epithelial cells and macrophages - Yanru Liu; Hong Yu; Jia He; Jianyin Li; Denggao Peng (PLoS ONE, 2025)
The current lack of a straightforward and convenient modeling approach to simulate the onset of acute lung injury (ALI) has impeded fundamental research and hindered the screening of therapeutic drugs in coronavirus disease 2019 (COVID-19). The co-cultured human pulmonary alveolar epithelial cells (HPAEpics) and alveolar macrophages (AMs) were exposed to the complete medium, three concentrations of recombinant spike S1 protein (0.1, 1, and 10 μg/mL), or lipopolysaccharide (LPS) (10 μg/mL). The cells were harvested at 1, 2, and 3 days post-exposure. Lactate dehydrogenase (LDH) release, and IL-6, TNF-ɑ, and malondialdehyde (MDA) production were quantified and compared. Compared to those exposed to medium, co-cultures of HPAEpics and AMs exposed to a concentration of S1 protein at 10 μg/mL demonstrated significantly increased levels of LDH release (22.9% vs. 9.1%, and 25.7%), IL-6 (129 vs. 74, and 110 pg/mg of protein), and TNF-ɑ (75 vs. 51, and 86 pg/mg of protein) production, and similar to those exposed to LPS. However, no statistically significant differences were observed in MDA production. Compared to those harvested at 1 or 2 days post-exposure, co-cultured cells harvested at 3 days post-exposure exhibited increased levels of LDH release (23.4% vs. 14.9%, or 16.7%), IL-6 (127 vs. 81, or 97 pg/mg of protein) and MDA (5.6 vs. 3.2, or 3.8 nmol/mg of protein) production, but exhibited lower TNF-ɑ (58 vs. 79 pg/mg of protein) production than those harvested at 2 days post-exposure. After 3 days of exposure, co-cultures of HPAEpics and AMs showed significantly increased levels of LDH release (25.3% vs. 18.4%), and MDA production (5.5 vs. 4.3 nmol/mg of protein) compared to HPAEpics monocultures, and increased levels of LDH release (25.3% vs. 13.8%), IL-6 (139 vs. 98 pg/mg of protein) and MDA (5.5 vs. 4.7 nmol/mg of protein) production, and decreased TNF-ɑ (59 vs. 95 pg/mg of protein) production compared to AMs monocultures. Conclusions: The exposure to a concentration of S1 protein at 10 μg/mL in co-cultures of HPAEpics and AMs induced significant injury and inflammation three days post-exposure. This methodology for establishing a COVID-19-associated ALI model may have promising potential applications and value.